がんサバイバーシップ - 山内, 英子 (Tairyoku kagaku. Japanese journal of physical fitness and sports medicine, 2018)
It had been considered Cancer as a deadly disease. Due to advancement of cancer treatment, Cancer is positioned as a chronic disease and the number of cancer survivors is increasing. Our society needs to consider cancer survivorship. Cancer care enters in the next stage. Cancer survivorship have to be considered by what stage the patient is and what aspect the patient needs to be supported. Four aspects would be divided into physical, psychology, social and spiritual. Four stages are acute stage of survival, extended stage of survival, permanent stage of survival and final stage of survival. As a team, we have to pay more attention for quality of life of patients and their family, even after their cancer treatments.